Propuesta de reforestación línea de transmisión eléctrica Tarbaca-Parrita, Tramo San Francisco de León Cortés-Parrita - Vargas-Quispe, José Javier (Instituto Tecnológico de Costa Rica, 2002)
This research offers the guidelines for the implementation of a reforestation process in the areas affected by the construction of the electric power lines in Lindora-Parrita. The proposal originates as an alternative to the mitigation measures for the environmental impacts described in the Environmental Impact Study of the construction of the Electric Power Lines. These measures will contribute with the improvement of the landscape and the environment and also the wildlife. 37 landowners within the area accepted five reforestation models. These models propose the use 29 native trees species. The species were chosen taking into account the needs of the landowners. They were distributed in the altitudinal strata present in the area. Costs estimates were calculated and they will be paid by the institution in charge of building the power lines (ICE acronyms in Spanish for Instituto Costaricense de Electricidad). Six economic scenarios were elaborated for the execution of this reforestation process. The criteria was the production or purchase of seedlings, transportation to the reforestation sites, activities for the establishment and maintenance. Finally, commercial grafted fruit trees delivery was added to the proposal as a mean to increase the landowners incomes and a food supply in the middle term.
Proyecto de Graduación (Bachillerato en Ingeniería Forestal) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2002.
Keywords: Mitigación; Impacto ambiental; Árboles; Cultivos; Frutales; Erosión